17th IEEE International Conference on Micro Electro Mechanical Systems. Maastricht MEMS 2004 Technical Digest
DOI: 10.1109/mems.2004.1290683
|View full text |Cite
|
Sign up to set email alerts
|

Surface polishing of three dimensional micro structures

Abstract: A new polishing technique for three dimensional micro structures using magnetorheological (MR) fluid is presented. Among various fabrication technologies of micro devices, some processes such as electroplating and wet etching which are widely used, give usually rough surface. However, there has been no polishing technique useful to micro structures, while various existing polishing methods are applicable only to flat surfaces or macro scaled stmctures. In this study, three dimensional micro channel smctures ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…MRF is being actively applied in magnetic field assisted finishing. Previous research efforts have reported the development of several new magnetic field assisted finishing techniques with MRF [1][2][3]. These processes are proposed for uses for external surfaces of optics, silicon products and micro structures.…”
Section: Introductionmentioning
confidence: 99%
“…MRF is being actively applied in magnetic field assisted finishing. Previous research efforts have reported the development of several new magnetic field assisted finishing techniques with MRF [1][2][3]. These processes are proposed for uses for external surfaces of optics, silicon products and micro structures.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, machining and erosive manufacturing methods cause rough surfaces, impair the glass at the machining point and often require a finishing (Belloy et al 2002;Lim 2004). Analogous limitations were considered for etching processes.…”
Section: Discussionmentioning
confidence: 99%
“…Weiterhin gibt es eine Reihe von seriellen Verfahren. Diese sind meist mit höheren Stückkosten verbunden oder sie schädigen das Glas an der Oberfläche [8,9,10,11].…”
Section: Introductionunclassified